Digital Inequality in a Developing Context: A Multifaceted Approach - Nobert R. Jere (https://orcid.org/0000-0001-8966-2753); Gardner Mwansa (https://orcid.org/0000-0003-3827-9783); Memory Ranga (https://orcid.org/0000-0002-8970-4789); Attlee M. Gamundani (https://orcid.org/0000-0003-1195-366X); Pardon B. Maoneke (https://orcid.org/0000-0002-7086-0044); William T. Vambe (https://orcid.org/0000-0003-0516-1260); Tanaka L. Jere (https://orcid.org/0000-0002-4825-0389); Obert Matarirano (https://orcid.org/0000-0001-5127-1028); Misheck Musaigwa (https://orcid.org/0000-0002-1474-5949); Thandokazi Mfikoyi (https://orcid.org/0000-0002-6640-090X); Sibulele Yawa (https://orcid.org/0009-0000-3404-7120); Bulelwa Mkabile-Masebe (https://orcid.org/0000-0002-8803-8526); et al. (AOSIS, 2025)
Digital inequality in a developing context: A multifaceted approach critically explores the complex and persistent nature of the digital divide in South Africa, addressing a notable gap in existing scholarship. Drawing on secondary data, the book examines how digital inequalities manifest across key sectors such as education, healthcare, and agriculture – sectors vital to national development and individual well-being. These disparities are shaped by intersecting socio-economic, technical, and geographical factors, particularly the urban–rural divide. The volume underscores the importance of infrastructure development, digital literacy, affordability, and equitable access as central to bridging the digital gap. It argues that without targeted and sustained interventions in these areas, digital inequality will continue to hinder socio-economic progress and deepen existing structural inequalities. This scholarly book offers fresh perspectives and practical insights for researchers, policymakers and practitioners seeking to advance digital inclusion in developing contexts.